Florfenicol Resistance in Enterobacteriaceae and Whole-Genome Sequence Analysis of Florfenicol-Resistant Leclercia adecarboxylata Strain R25. (1st October 2019) - Ying, Yuanyuan; Wu, Fei; Wu, Chongyang; Jiang, Yi; Yin, Min; Zhou, Wangxiao; Zhu, Xinyi; Cheng, Cong; Zhu, Licheng; Li, Kewei; Lu, Junwan; Xu, Teng; et al.
Abstract : Due to inappropriate use, florfenicol resistance is becoming increasingly serious among animal respiratory tract and gut bacteria. To detect the florfenicol resistance mechanism among Enterobacteriaceae bacteria, 292 isolates from animal feces were examined. The agar dilution method was conducted to determine the minimum inhibitory concentration (MIC) for florfenicol, and polymerase chain reaction (PCR) was performed to detect florfenicol resistance genes. To further explore the molecular mechanism of florfenicol resistance, the whole-genome Leclercia adecarboxylata R25 was sequenced. Of the strains tested, 61.6% (180/292) were resistant to florfenicol, 64.4% (188/292) were positive for floR, and 1.0% (3/292) for cfr . The whole-genome sequence analysis of L. adecarboxylata R25 revealed that the floR gene is carried by a transposon and located on a plasmid (pLA-64). Seven other resistance genes are also encoded on pLA-64, all of which were found to be related to mobile genetic elements. The sequences sharing the greatest similarities to pLA-64 are the plasmids p02085-tetA of Citrobacter freundii and p234 and p388, both from Enterobacter cloacae . The resistance gene-related mobile genetic elements also share homologous sequences from different species or genera of bacteria. These findings indicate that floR mainly contributes to the high rate of florfenicol resistance among Enterobacteriaceae. The resistance gene-related mobile genetic elements encoded by pLA-64 may be transferred among bacteria of different species or genera, resulting in resistance dissemination.